Study of the interplay among internal and external barriers to GSCM in the Indian leather industry using the total ISM and MICMAC methodology - Manoj Kumar; Rao T Joji (Cogent Business & Management, 2023)
Green Supply Chain Management (GSCM) has received growing attention in the last few years. Due to public awareness, economic, environmental, or legislative reasons, the requirement of GSCM has increased. The Indian leather industry is considered to be the most polluted industry in India in terms of all forms of pollution, i.e. water, land, and air. In the recent past, the Indian leather industry has been changing basic assumptions. The world's largest exporter of leather is currently becoming a net importer of the bovine hide. Manufacturing industries have started adopting the green concept in their supply chain management recently to focus on environmental issues. However, industries still struggle to identify the relationship between internal and external barriers hindering green supply chain management implementation. In this context, this study aims to develop a structural model between internal and external barriers to implementing GSCM in the Indian leather industry. To assess the link between internal and external barriers to GSCM in the Indian leather sector, empirical research was carried out utilizing a Multi-Criteria Decision Making (MCDM) method called Interpretive Structural Modeling (ISM). ISM is a useful approach for understanding the complex relationships between various internal and external barriers and their hierarchies in the context of green supply chain management (GSCM) adoption. It can be used to identify the key barriers that influence the effective adoption of GSCM in the Indian leather industry, as well as the interdependencies between these barriers. This can help GSCM decision-makers in the Indian leather industry to better understand the challenges and opportunities for implementing sustainable practices throughout their supply chain and to develop effective strategies for addressing them. Additionally, ISM can be used to identify the key drivers and barriers to GSCM adoption, which can inform the development of targeted interventions to promote sustainable practices in the Indian leather sector. The findings indicate that inconsistent quality and lack of motivational laws are the most crucial barriers to overcoming the remaining obstacles and implementing GSCM successfully in the Indian leather sector.
Keywords: 650; barriers to implementing GSCM; green supply chain management; interpretive structural modeling